Efforts To Transform Community Services Through The Pringrejo E-Law Smart Village Program In The Era of Society 5.0 - Syirfan, Muhammad Addi; Fu’adah, Shofwatul; Hedra, Helmalia; Widodo, Rafatavera Yeremia; Ardani, Ahmad; Syakirin, Mohammad Bahrus (Universitas Negeri Semarang, 2023)
Community services are related to regional development which is also related to national development. The acceleration of the transformation of the quality of community services can actually affect the level of community welfare in a better direction in the era of Society 5.0. The formulation of the problem encountered is how is the transformation of public services in the Era of Society 5.0? and how is the Pringrejo E-Law Smart Village program an effort to transform Era Society 5.0 services? The formulation of the problem was answered by the Pringrejo UNIKAL KKN service method through five stages, namely observation, data collection, preparation of physical programs, trials – evaluation, and finalization. The result found is that community service programs are very important to be transformed with technology to support the increasing needs of the community. The intermingling is also in accordance with the concept of the current Society 5.0 era. The Pringrejo E-Law Smart Village program is here to be a solution and answer to the transformation of digital technology-based community services. Thus, the Pringrejo E-Law Smart Village program, which is a website-based smart law village program, is a solution to the transformation of community services in the era of Society 5.0.